Effect of Xenon Anesthesia Compared to Sevoflurane and Total Intravenous Anesthesia for Coronary Artery Bypass Graft Surgery on Postoperative Cardiac Troponin Release: An International, Multicenter, Phase 3, Single-blinded, Randomized Noninferiority Trial. (December 2017) - Hofland, Jan; Ouattara, Alexandre; Fellahi, Jean-Luc; Gruenewald, Matthias; Hazebroucq, Jean; Ecoffey, Claude; Joseph, Pierre; Heringlake, Matthias; Steib, Annick; Coburn, Mark; Amour, Julien; Rozec, Bertrand; et al.
Abstract : Background: Ischemic myocardial damage accompanying coronary artery bypass graft surgery remains a clinical challenge. We investigated whether xenon anesthesia could limit myocardial damage in coronary artery bypass graft surgery patients, as has been reported for animal ischemia models. Methods: In 17 university hospitals in France, Germany, Italy, and The Netherlands, low-risk elective, on-pump coronary artery bypass graft surgery patients were randomized to receive xenon, sevoflurane, or propofol-based total intravenous anesthesia for anesthesia maintenance. The primary outcome was the cardiac troponin I concentration in the blood 24 h postsurgery. The noninferiority margin for the mean difference in cardiac troponin I release between the xenon and sevoflurane groups was less than 0.15 ng/ml. Secondary outcomes were the safety and feasibility of xenon anesthesia. Results: The first patient included at each center received xenon anesthesia for practical reasons. For all other patients, anesthesia maintenance was randomized (intention-to-treat: n = 492; per-protocol/without major protocol deviation: n = 446). Median 24-h postoperative cardiac troponin I concentrations (ng/ml [interquartile range]) were 1.14 [0.76 to 2.10] with xenon, 1.30 [0.78 to 2.67] with sevoflurane, and 1.48 [0.94 to 2.78] with total intravenous anesthesia [per-protocol]). The mean difference in cardiac troponin I release between xenon and sevoflurane was −0.09 ng/ml (95% CI, −0.30 to 0.11; per-protocol: P = 0.02). Postoperative cardiac troponin I release was significantly less with xenon than with total intravenous anesthesia (intention-to-treat: P = 0.05; per-protocol: P = 0.02). Perioperative variables and postoperative outcomes were comparable across all groups, with no safety concerns. Conclusions: In postoperative cardiac troponin I release, xenon was noninferior to sevoflurane in low-risk, on-pump coronary artery bypass graft surgery patients. Only with xenon was cardiac troponin I release less than with total intravenous anesthesia. Xenon anesthesia appeared safe and feasible. Abstract : This randomized prospective study compared xenon-, sevoflurane-, and propofol-based anesthesia in patients undergoing elective on-pump coronary artery bypass graft surgery. With regard to postoperative cardiac troponin I release, xenon was noninferior to sevoflurane in low-risk, on-pump coronary artery bypass graft surgery patients. Only with xenon was cardiac troponin I release less than with total intravenous anesthesia. Xenon anesthesia appeared safe and feasible.Supplemental Digital Content is available in the text.